Mystic on a Tilting Stage: Julian of Norwich’s Performance of English Visionary Devotion - Elizabeth F. Perry (Religions, 2023)
Julian of Norwich’s performance within her longer Revelations of Divine Love involves layers of authorizing and devotional steps that frame it as a gift for her community. She presents herself not as an author, but as a revelator, in step with John’s acts of unveiling his visions and dialogue with the divine in the Biblical Revelations. Examining Julian’s act of presenting her visions in writing demonstrates how her daring yet insistently orthodox visions handle issues of spiritual authority and individual faith made urgent by the rise of Lollardy. My work with Julian’s Revelations is the foundation for a wider argument about the interchange between vernacular mysticism and public devotion through their use of affective piety and the performance of spiritual dialogue. In this article, I examine Julian of Norwich’s Revelation of Divine Love to determine how it works as contemplative drama. I also look at The Mirror of the Blessed Life of Christ and The Cloud of Unknowing to set up Julian’s performance of contemplative devotion and the potential pitfalls of a pious English readership. Julian’s revelations demonstrate where interior contemplation is transformed into collective acts of devotion.